A novel mutation in ABCD1 unveils different clinical phenotypes in a family with adrenoleukodystrophy. (September 2017) - Margoni, M.; Soli, F.; Sangalli, A.; Bellizzi, M.; Cecchini, E.; Buganza, M.
Abstract: X-linked adrenoleukodystrophy (X-ALD) is the most common peroxisomal disorder. The disease is the consequence of mutations in the ABCD1 gene that encodes the peroxisomal membrane protein ALDP which is involved in the transmembrane transport of very long-chain fatty acids. We describe a family with six members carrying a novel heterozygous mutation IVS4+2T>A (c.1393+2T>A) of the ABCD1 gene, highlighting the wide range of phenotypic manifestations of ALD and the importance of genetic screening before any pregnancy in asymptomatic women whose carrier status is unknown.